Глава 1.2. Відтермінування виконання, зміна чи встановлення способу і порядку виконання рішення в цивільному судочинстві - Навроцька, Юлія Вячеславівна; Воробель, Уляна Богданівна (Цивільний та виконавчий процес: міжгалузеві зв’язки. Особливості розгляду судами певних категорій справ та виконання судових рішень. Монографія, 2024)
In modern civil proceedings, the issues of postponement and installment of enforcement, change or establishment of the method and procedure for enforcement of court decisions are some of the aspects that determine the efficiency and fairness of justice. In the context of certain categories of civil cases, such institutions are of particular importance, requiring research and analysis of case law to understand their impact and consequences.The article examines the processes associated with changing the conditions for enforcement of court decisions in civil cases. The authors analyze the legal framework determining the court' s competence to resolve issues related to the postponement of the enforcement of court decisions and changes in the conditions of their execution. The authors examine the basic principles and criteria by which a court determines whether to postpone the enforcement of a judgment.The study of postponement and deferral of enforcement of court decisions, change or establishment of the method and procedure for enforcement of judgments in civil proceedings allows identifying trends characterizing the court' s actions in various categories of cases, and also identifying the main factors influencing the decision-making process regarding postponement or deferral of enforcement, change orestablishment of the method and procedure for enforcement of judgments in civil proceedings.The article analyses interesting and trendy examples of resolving issues related to postponement or deferral of enforcement of a courjudgment, summarizes general approaches to resolving such motions, and identifies legal positions of higher courts used by courts of first instance and appellate courts when resolving issues related topostponement of enforcement.The authors also analyze the case law on establishing or changing the method and procedure for enforcement of judgments in civil proceedings. The authors conclude that it is impossible to distinguish a certain typology of cases in which the court considered the issues of establishing or changing the method and procedure of enforcement due to the diversity of legal requirements. The author establishes that inpractice, persons try to change the chosen method of protection rather than the procedure for enforcement of a judgment, which is unacceptable at the stage of judgment enforcement. The authors emphasize that in order to change the method and procedure for enforcement of judgments, it is necessary to have sufficient evidence and justification of their exclusivity, and to avoid attempts to change the method of protection provided by law.Further study of these issues will contribute to the development of judicial practice, improvement of the processes of enforcement of court decisions and increase of public confidence in the legal system.